Effects of abnormal muscle forces on prenatal joint morphogenesis in mice - Rolfe, Rebecca; Murphy, Paula (My University, 2019)
Fetal movements are essential for normal development of the human skeleton. When fetal movements are reduced or restricted, infants are at higher risk of developmental dysplasia of the hip and arthrogryposis (multiple joint contractures). Joint shape abnormalities have been reported in mouse models with abnormal or absent musculature, but the effects on joint shape in such models have not been quantified or characterized in detail. In this study, embryonic mouse forelimbs and hindlimbs at a single developmental stage (Theiler Stage 23) with normal, reduced, or absent muscle were imaged in three-dimensions. Skeletal rudiments were virtually segmented and rigid image registration was used to reliably align rudiments with each other, enabling repeatable assessment and measurement of joint shape differences between normal, reduced-muscle and absent-muscle groups. We demonstrate qualitatively and quantitatively that joint shapes are differentially affected by a lack of, or reduction in, skeletal muscle, with the elbow joint being the most affected of the major limb joints. Surprisingly, the effects of reduced muscle were often more pronounced than those of absent skeletal muscle, indicating a complex relationship between muscle mass and joint morphogenesis. These findings have relevance for human developmental disorders of the skeleton in which abnormal fetal movements are implicated, particularly developmental dysplasia of the hip and arthrogryposis.
PUBLISHED
Keywords: Biomechanics; Fetal movements; Image registration; Joint development; Joint shape; Genes & Society; Developmental Biology